DAMPAK CONTENT MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN - Farid Maulana; Juharsah; Yusuf; Hartini (Jurnal Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of content marketing on Instagram and brand image on consumer purchasing decisions of Yotta beverage products in Kendari City. Using a descriptive quantitative approach, data were collected through questionnaires to 96 Yotta consumers who are active on Instagram (@yotta_id) using the purposive sampling method. The analysis was carried out using multiple linear regression. The results of the study indicate that content marketing on Instagram and brand image simultaneously have a positive and significant effect on consumer purchasing decisions. Partially, content marketing on Instagram has a positive and significant effect on purchasing decisions. The same applies to brand image, which has also been shown to have a positive and significant effect on purchasing decisions